Маленький принц - Сент-Экзюпери Антуан (Эксмо, 2023)
Экземпляры: Селтинская детская библиотека (20240917) / Инвентарный номер: 210625 / Цена: / Сис.шифр: 84(4Фра) / Авт.знак: С 31 / ГРНТИ: 17.82.93 / ББК: 84(4Фра)